Estudo da poluição hídrica do complexo estuarino de Paranaguá–PR, causado pela presença de HPAS, n-alcanos e contaminantes emergentes - Lima, Bárbara Alves (2019)
The rivers of the Souht of Brazil have their alarm conditions in terms of quality, having some of them already been framed in the critical state. Contamination of water resources has been a reality for several Brazilian areas. The Paranaguá Estuary Complex, belonging to the Paraná Coastal Basin, has waters classified as class 2 in the course of the Itiberê river, and brackish water class 1 from the mixing zone, having in its regions the Port of Paranaguá, and an intense flow of boats that travel between the rivers of the region, besides suffering with the urbanization present in the surroundings of the river. Polycyclic Aromatic Hydrocarbons and nalkanes in the water and sediment of the Paranaguá Estuary Complex, in addition to some classes of contaminants of interest emerging in the water. For this purpose, 4 samples of water and sediments were carried out at selected points, going to the urbanized Itiberê river, characterized by urbanization, up to the tip of the Uba, characterized by a small anthropic activity. The presence of PAH in pyrogenic predominant sediment was confirmed, however, there was no signal in the water, since the compound has the lipophilic function. The last n-alkanes in the water, however, were more intense in the sediment samples, and received as a result the mixed contamination, characteristic of the mangrove area. Finally, the emerging contaminants may be larger than the Itiberê river, possibly due to the intense urbanization of the site.